How do I see the Tuvan economy after the construction of "Kyzyl – Kuragino” railroad - Hertek, Chayana E. (The New Research of Tuva, 2012)
Article took the 2nd place in "Models for economic development of Tuva” essay contest held in 2012 by the Plenipotentiary Representative Office of Tuva in Moscow. Author reflects on the advantages that railroad, connecting Kyzyl with the rest of the country, will bring to the Republic.
Keywords: Tuva; Russia; roads; transport; railroad; Kyzyl – Kuragino; economy